2011
DOI: 10.1021/ja105696p
|View full text |Cite
|
Sign up to set email alerts
|

Organoactinides Promote the Dimerization of Aldehydes: Scope, Kinetics, Thermodynamics, and Calculation Studies

Abstract: Surprising catalytic activities have been found for the actinide complexes Cp*(2)ThMe(2) (1), Th(NEtMe)(4) (2), and Me(2)SiCp''(2)Th(C(4)H(9))(2) (3) toward oxygenated substrates. During the catalytic dimerization of benzaldehydes to their corresponding esters, complexes 1 and 2 gave 65 and 85% yield in 48 h, respectively, while the geometry-constrained complex 3 gave 96% yield in 24 h. Exploring the effect of substituents on benzaldehyde, it has been found that, in general, electron-withdrawing groups facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 121 publications
0
57
0
2
Order By: Relevance
“…Moreover, a KIE measurement of 6.0 suggests that CÀH bond activation is ratedetermining (Scheme 5 b). [19] On the basis of these initial studies and literature reports, we propose the mechanism shown in Scheme 6. [20] Ketone 3 d binds to nickel to form complex 8 a, which can coordinate to an aldehyde (1) to give intermediate 8 b. Oxidative addition to the aldehyde CÀH bond generates 8 c, which reduces the hydrogen acceptor 3 d to yield acyl nickel alkoxide 8 d. [21] Ligand exchange with the nucleophile affords 8 e, and reductive elimination provides the final product.…”
mentioning
confidence: 89%
“…Moreover, a KIE measurement of 6.0 suggests that CÀH bond activation is ratedetermining (Scheme 5 b). [19] On the basis of these initial studies and literature reports, we propose the mechanism shown in Scheme 6. [20] Ketone 3 d binds to nickel to form complex 8 a, which can coordinate to an aldehyde (1) to give intermediate 8 b. Oxidative addition to the aldehyde CÀH bond generates 8 c, which reduces the hydrogen acceptor 3 d to yield acyl nickel alkoxide 8 d. [21] Ligand exchange with the nucleophile affords 8 e, and reductive elimination provides the final product.…”
mentioning
confidence: 89%
“…In recent decades, extensive studies have been carried out to improve the reaction yield and expand the substrate scope. [2] Various catalysts, including alkali metal, [1,3] boric acid, [4] actinides, [5] lanthanide [6] and transition-metal complexes [7,8] (such as Rh [7a] and Os complexes [7b] ), have been utilized in Tishchenko reactions. Nonetheless, traditional Tishchenko reactions are mainly limited to homocouplings between two molecules of the same substrate, whereas cross-coupling between two different substrates is relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…27 The high yield of dimer generated from this substrate illustrates the lower energetic pathway of protolytic cleavage in comparison to migratory insertion into the actinide−vinyl bond. This is corroborated by the small quantities of product formed from the additional insertion into this intermediate, evident by the formation of only small amounts of trimer 6a (≤7%), similarly occurring from a headto-tail insertion.…”
Section: ■ Results and Discussionmentioning
confidence: 93%